Submerged Membrane Photo Reactor (SMPR) with Simultaneous Photo Degradation and TiO2 Catalyst Recovery for Efficient Dyes Removal - Dessy Ariyanti; Filicia Wicaksana; Wei Gao (Department of Chemical Engineering, Universitas Gadjah Mada, 2021)
In this study, a polyvinylidene difluoride (PVDF) hollow fiber membrane module incorporated with TiO2 was submerged into a photocatalytic reactor to create a hybrid photocatalysis with membrane separation process (a submerged membrane photoreactor, SMPR), for advanced dyes wastewater treatment. The SMPR performance was assessed by the degradation of single component Rhodamine B (RhB) and degradation of mixed dyes (RhB and Methyl orange (MO)) in a binary solution. Several operational parameters such as the amount of catalyst loading, permeate flux, and the effect of aeration were studied. Fouling tendency on the membrane was also investigated to determine the optimum operating conditions. The results show that the synergetic effect of the low catalyst loading and permeate flux creates the environment for optimum light penetration for high photocatalytic activity as the hybrid system with low catalyst loading (0.5 g/L) and 66 L/m2h of flux with aeration at 1.3 L/min has proven to increase the photocatalysis performance by 20% with additional catalyst recovery. In addition, applying the low catalyst loading and flux permeate with aeration brings minimal fouling problems.